Solidarity in Local and Multicultural Communities in the South of Russia - G. Volkov, Yuriy (2019)
The article presents the results of the social research of solidarity in the South Russian multi-ethnic region as an essential structure of mental programs of social behavior in local communities. The study of cognitive, axiological and conative aspects of solidarity made it possible to draw the conclusion that in the South of Russia, just as in Russian society in general, social solidarity, being at a very low level, mainly takes forms of the “lower” (micro-social) self-organization and mutual aid, associated with the self-assertion by citizens, as well as upholding of their economic and environmental interests.